A backstepping high-order sliding mode voltage control strategy for an islanded microgrid with harmonic/interharmonic loads. (January 2017) - Mahdian Dehkordi, Nima; Sadati, Nasser; Hamzeh, Mohsen
Abstract: This paper presents a new nonlinear voltage control strategy based on backstepping control and a high-order sliding mode differentiator for an islanded microgrid. The microgrid consists of multiple distributed generation (DG) units with an arbitrary configuration that can be parametrically uncertain or topologically unknown. The proposed controller robustly regulates the microgrid voltages in the presence of parametric uncertainties, unmodeled dynamics, load imbalances, and nonlinear loads with harmonic/interharmonic currents. In contrast to existing methods, the controller does not need to know the frequency of harmonic and interharmonic current of microgrid loads that lead to the reduction of the steady-state error of the voltage controller in the frequency of unknown harmonics and interharmonics. The MATLAB/SimPowerSystems toolbox has verified the proposed control strategy's performance. Abstract : Highlights: A novel backstepping control method is proposed to robustly regulate microgrid voltages in the presence of nonlinear loads. The Lyapunov method is used to prove asymptotic stability of the closed-loop system. If the harmonic/interharmonic frequency of loads is changed, altering the control structure is not necessary. The proposed controller is compared with PR controller. Case studies verify that the proposed method exactly compensates for the harmonic/interharmonic currents of nonlinear loads.